The Influence of Shopee Live Promotional Media on Product Purchase Decisions - Maria, Vera; Putri, Narita Maulidya; Putri, Zahwa Farellia Nindia (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The purpose of this research is to analyze purchasing decisions using promotional media conducted through the online marketplace platform Shopee Live or streaming, which allows sellers and consumers to interact in real time. This research also discusses consumer behavior in relation to purchasing decisions.